Endovascular Embolization in the Treatment of Epistaxis. (12th February 2019) - Huyett, Phillip; Jankowitz, Brian T.; Wang, Eric W.; Snyderman, Carl H.
Abstract : Objective: The cost‐effectiveness of endovascular embolization (EE) for intractable epistaxis has been questioned, especially as endoscopic surgical techniques have become standard of care at many institutions. Our objectives were to review the safety profile and effectiveness of EE for epistaxis. Study Design: Retrospective case series. Setting: Tertiary care hospital. Subjects: There were 54 patients and 64 unique encounters. Patients were 66.7% male, with a mean age of 64.5 years. Bleeding disorders were present in 18.8%, hypertension was present in 71.7%, and 61.1% were on anticoagulant/platelet drugs. Methods: Charts of patients undergoing EE for epistaxis between 2005 and 2015 were retrospectively reviewed. Results: The immediate bleeding control rate was 92.6%. Three patients died within 1 week of EE and were excluded from further analysis. Overall, 64.7% of the remaining patients had no further episodes of epistaxis. Thirteen patients (25.4%) rebled within 1 week, 11 of whom required repeat EE or operative control. Five patients (9.8%) rebled more than 1 week following the procedure with 4 requiring repeat EE or operative control. The major complication rate was 7.4% and included transient stroke, diplopia, facial skin necrosis, and extraperitoneal hemorrhage. Conclusion: While the immediate success rate of EE for epistaxis was comparable to the literature, the overall short‐ and long‐term rebleed rate was high in this selected population. The results suggest that patients who are referred for EE represent a high‐risk group with increased risk of repeat hemorrhage and morbidity. Patients who undergo EE for epistaxis should be carefully monitored for complications, including repeat hemorrhage.